Die Sprache der Judenfeindschaft im 21. Jahrhundert - Schwarz-Friesel, Monika (Europäisch-jüdische Studien. Beiträge, 2013)
This study considers the question of how specific ideas about Jews are constructed and activated. At which point can a statement be regarded as anti-Semitic? The two authors examine the various verbal manifestations of current anti-Semitism and the mental images on which these are based, applying both a historical perspective and the perspective of linguistic and cognitive science. Keywords: Anti Semitism; Anti Zionism; Cognitive Science; Linguistic Analysis; Central Council.